Dairy calf and heifer research at KSU - J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1990)
At Kansas State University, we are conducting research concerning nutrition and feeding management of calves, heifers, and dairy steers with emphasis in the following areas: 1) development of feeds and management practices to stimulate rumen development and allow earlier weaning, concomitant with satisfactory growth; 2) vitamin supplementation to improve performance of growing dairy animals, with emphasis on increasing efficiency of the immune system; 3) determination of nutrients needed by growing heifers to achieve desired rates of growth required to reach adequate size at freshening at 22 to 24 mo of age, without getting too fat; 4) study of feeding programs designed to produce lean, tender, flavorful meat from surplus dairy bulls, with emphasis on methods to monitor body composition in the live animal; and 5) investigation of protein sources for milk replacers.; Dairy Day, 1990, Kansas State University, Manhattan, KS, 1990; The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: Dairy Day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-148-S; Report of progress (Kansas Agricultural Experiment Station); 608; Dairy calf; Dairy; Heifer; Research